Diseño de un sensor para campo eléctrico con el fin de identificar una descarga atmosférica. - Guanoluisa Arciniega, Walter David (2020)
This project is about prototypes of sensors with the purpose of detecting an electric field, for which three models of capacitive sensors and an electronic circuit were developed, which together, measure the level of the electric field and detect the disturbance of this magnitude in the environment. To validate the devices built, measurements were made on a transmission line according to the IEEE 644 regulation “Procedures for Measurement of Power Frequency Electric and Magnetic Fields from AC Power Lines” and the results obtained were contrasted based on data collected with a standard sensor. The methodology used is based on the analysis of the acquired data, in which adjustment methods were applied and in this way a relationship with a reduced error rate between the acquired data and the standard sensor could be reached, allowing the detection of discharges atmospheric as well as the level of the electric field. Finally, the economic analysis, conclusions and recommendations that show the main aspects of the developed project are presented.